Analysis of delamination of composite laminates via extended finite element method based on the layerwise displacement theory and cohesive zone method - Santos, Matheus VM (2021)
Composite laminates are being more employed as fundamental structures due to its low weight and high stiffness. To predict the material response in presence of damage can be demanding due to composite’s complex nature. Hence, superior computational models should be further investigated to speculate a more accurate composite behavior. This paper proposes an extended finite element procedure, based on the layerwise displacement theory, to simulate delamination to composite laminate. It is assumed a cohesive behavior to the damaged domain, described by a traction separation law. An extra degree of freedom associated to the strong discontinuity (delamination) is added at each layer top and bottom surface for out-of-plane displacement. This extra degree of freedom is only active on the failed nodes. To validate the model, a pre-delaminated composite analysis is performed and compared to results already reported in the literature. In addition, all stress components can be precisely calculated due to layer wise displacement field assumption, without any concern about the membrane and shear locking, not to mention its greater computational efficiency when compared to equivalent three-dimensional elements. Therefore, in the present work, it is shown the limitations and potentialities when a cohezive formulation is combined to extended finite element method using a new kind of approach. Additionally, this formulation makes easier to model delaminations using finite element method keeping a good accuracy without the need of cumbersome finite element models.